Advancing culture of living with landslides. Volume 2, - Mikoš, Matjaž; Tiwari, Binod; Yin, Yueping; Sassa, Kyoji (Springer, 2017)
This volume contains peer-reviewed papers from the Fourth World Landslide Forum organized by the International Consortium on Landslides (ICL), the Global Promotion Committee of the International Programme on Landslides (IPL), University of Ljubljana (UL) and Geological Survey of Slovenia in Ljubljana, Slovenia from May 29 to June 2,. The complete collection of papers from the Forum is published in five full-color volumes. This second volume contains the following: - Two keynote lectures - Landslide Field Recognition and Identification: Remote Sensing Techniques, Field Techniques - Landslide Investigation: Field Investigations, Laboratory Testing - Landslide Modeling: Landslide Mechanics, Simulation Models - Landslide Hazard Risk Assessment and Prediction: Landslide Inventories and Susceptibility, Hazard Mapping Methods, Damage Potential Prof. Matjaž Mikoš is the Forum Chair of the Fourth World Landslide Forum. He is the Vice President of International Consortium on Landslides and President of the Slovenian National Platform for Disaster Risk Reduction. Prof. Binod Tiwari is the Coordinator of the Volume 2 of the Fourth World Landslide Forum. He is a Board member of the International Consortium on Landslides and an Executive Editor of the International Journal "Landslides". He is the Chair-Elect of the Engineering Division of the US Council of Undergraduate Research, Award Committee Chair of the American Society of Civil Engineering, Geo-Institute's Committee on Embankments, Slopes, and Dams Committee. Prof. Yueping Yin is the President of the International Consortium on Landslides and the Chairman of the Committee of Geo-Hazards Prevention of China, and the Chief Geologist of Geo-Hazard Emergency Technology, Ministry of Land and Resources, P.R. China. Prof. Kyoji Sassa is the Founding President of the International Consortium on Landslides (ICL). He is Executive Director of ICL and the Editor-in-Chief of International Journal"Landslides" since its foundation in 2004. IPL (International Programme on Landslides) is a programme of the ICL. The programme is managed by the IPL Global Promotion Committee including ICL and ICL supporting organizations, UNESCO, WMO, FAO, UNISDR, UNU, ICSU, WFEO, IUGS and IUGG. The IPL contributes to the United Nations International Strategy for Disaster Reduction and the ISDR-ICL Sendai Partnerships 2015-2025.
Includes author index.
Keywords: Landslides.; Landslide hazard analysis.; elektronické knihy; electronic books